Florística, estrutura e estádios sucessionais de fragmentos nativos da mata atlântica em Minas Gerais - Reis, Hermógenes (2007)
A floristic study was carried out in 4 forest fragments subjected to different treatments. Two fragments were subjected to a management plan (one of them for 14 years and the other for 9 years), the third one was clear cut and burnt 22 years ago, and the last fragment (control) for which there is no record of strong intervention. The objectives of this study were: to study the floristic composition in order to know the diversity; to determine the floristic similarity among the four fragments; to evaluate the structural behavior of the species in each fragment; to characterize the successional stages in relation to the species richness and diametric classes; to infer about the adherence of diametric distributions before and after the exploration of 2 forest fragments using the test of Kolmogorov-Smirnov. The studied areas correspond to 4 forest fragments located in the cities of Piranga and Diogo de Vasconcelos in the State of Minas Gerais. It was applied the systematic sampling, with the first plot set in an initial point of the forest and from there transects were established throughout each fragment. The number and distance of transects, and the distance between sampling plots varied with the form and size of each fragment. The inventoried individuals were those with a circumference at breast height (CBH) ≥ 15.70 cm, being also recorded the total height. In the fragments, 12,709 individuals were found, distributed in 397 species, 190 genus and 67 families. The Shannon´s diversity index varied from 3.91 (fragment 3) to 4.71 (fragment 4). Considering the floristic similarity, the method of Sorensen weas more rigorous than Jaccard, in discriminating sites. The four fragments are highly similar among them with index values above 44%. The basal area of the fragments varied from 12.71 to 28.45 m2.ha-1, with the highest value found in fragment 4. The density varied from 2,603 to 3,844 individuals, with the highest density found in fragment 3. The number of species varied from 160 (fragment 1) to 260 (fragment 4), with the latter showing the highest floristic diversity among all. The species with the the highest importance value index (IVI) were different for each fragment. Around 12% of the species were present in the four fragments. The early secondary species stood out before the others in all fragments, however shade-tolerant species are in good development. The diametric structure of the 4 fragments showed negative exponential form. According to the Kolmogorov-Smirnov test (5%) there was no correlation between distribution, before and after the exploration in the fragment 1, while in the fragment 2 the distribution before and after the exploration showed a positive correlation.